Fuerza y movimiento : la interpretación de los estudiantes - Sebastià, José M. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
In the present work we present the results of a study about students' interpretations concerning physical situations involving the concepts of movement and force. Using an appropriate methodology and instrumentation we obtained evidence that the general patterns of interpretation that students use in this area of physics differ greatly from the newtonian interpretation that is intented to be transmitted in physics courses. Taking a sample of Spanish students from the geographic areas of Madrid and Valladolid, and accounting for the education level, we verified the great weight of those interpretations, and that they are not replaced by the physics courses that the students have taken. Certain implications for the improvement of physics teaching derived from the obtained results are suggested in the final part of this article.